Sistema informacionnogo obepecenija kommerceskich fizkul'turno-sportivnych organizacij - Fillipov, S. S.; Voskresenskaja, N. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The basic purpose of the activity of commercial sports organizations (CSO) is getting profit according to the results of their work. Therefore the informational supply of the activity of such organizations should take into account this specific feature.